Intrapartum electrocardiogram alteration in fetuses with congenital heart disease: a case–control study. (November 2015) - Gay, Estelle; Bornallet, Géraldine; Gaucherand, Pascal; Doret, Muriel
Abstract: Objective: To assess if the fetal electrocardiogram especially ST segment is modified by congenital heart diseases: modifications in frequencies of the different ST events and modifications in signal quality. Study design: A retrospective case–control study, comparing frequencies of the different ST events and the quality of the signal between fetuses with congenital heart diseases and fetuses without congenital heart disease. From 2000 to 2011, fifty-eight fetuses with congenital heart disease had their heart rate recording using a STAN device during labor. Control group was fetuses who were born just before a case and had a STAN as a second line for intrapartum surveillance. Cases and controls were matched on parity, gestational age at birth, presence of growth restriction and umbilical artery pH. Frequencies of the different ST event and quality of the signal were first analyzed for the global labor recording, and then separately for the first and the second phase of labor. Results: No statistically significant difference in ST event frequencies between fetuses with congenital heart disease and the control group was found. Regarding the quality of the signal, 11.49% (±18.82) of recording time is a signal loss for fetus with congenital heart disease whereas only 5.18% (±10.67) for the control group ( p = 0.028). Conclusion: This is the first study investigating for intrapartum electrocardiogram modification in fetus with congenital heart disease. Congenital heart diseases do not modify frequencies of ST events.